Emîr es-San’ânî’de hadis usûlü ve rivâyet tahlili - Aydın, Elif (My University, 2018)
Emîr es-San’ânî’de Hadis Usûlü ve Rivâyet Tahlili isimli tez, 1099/ 1688–1182/ 1769 yılları arasında yaşamış, İslâmi ilimlerin hemen her sahasında yazdığı iriliufaklı 200’e yakın eseri olan ve bilhassa da Sübülü’s-selâm müellifi olarak tanınan,Yemen’li, Muhammed b. İsmail Emir es-San’ânî’yi tanıtmak ve hadisle ilgilifikirlerini tesbit ve tahlil etmek amacı ile hazırlanmıştır.Giriş ve üç bölümden oluşan tezin giriş bölümünde konu, yöntem vekaynaklar hakkında bilgi verilmiştir.İç karışıklıkların çok olduğu Yemen'de yaşayan Emîr es-San’ânî’nin dönemisosyal, siyasî ve ilmî açıdan incelenmiştir. Ardından San’ânî’nin hayatı, karşılaştığızorluklar, mücadelesi, ilmi kişiliği, bid'atler karşısındaki tavrı ve eserleri elealınmıştır.Hadis Usulü’ne Dair Görüşleri ile dikkat çeken San’ani’nin, râvininvasıfları, sahabe tanımı, ravi tenkidi, rivâyetlerin sıhhat açısından durumları ve rivâyeteserleri hakkındaki görüşleri ile kendinden önceki bazı âlimlere itirazları ortayakonulmuştur.Emir San’ânî’nin ''Hadis Tahlil Yöntemi, hadis ve sünnet kavramları, şerhmetodu, hadisleri delil olarak göstermesi, sened ve metin tenkidi ve hadisler arasındaihtilafları çözme metotları incelenmiştir.Değerlendirme ve konuyla ilgili tesbit ve tekliflerle araştırma son bulmuştur.

The dissertation titled “Usool al-Hadeeth (Science of Hadith) and the Analysis ofChain of Narrators according to Emir al-San’ani” is prepared to introduce Yamani savantMuhammad ibn Ismael Emir al-San’ani, and to identify and to analyze his views on hadith.Muhammad ibn Ismael Emir al-San’ani, who lived between 1099/ 1688-1182/ 1796, wroteabout 200 books and mainly known as the author of Subul as-Salaam.The dissertation is divided into an introduction and three parts. The introduction, isdedicated to provide information about subject, methodology and sources.The first part examines the time of Emir al-San’ani, who lived in the times of turmoilin Yaman, socially, politically, and from Islamic studies point of view. Then San’ani’s life,his struggles, his scholarship, his opinions on bidahs and his work are detailed.San’ani’s views Usool al-Hadith” received attention. The second part in thisdissertation includes San’ani’s views on narrator’s traits, his definition of sahabah, hiscriticism of narrators and their trustworthiness, his views on other books on narration, and hiscriticisms to earlier scholars.The third part is dedicated to investigation of Emir as-San’ani’s “Hadith AnalysisMethod”. His definition of hadith and Sunnah, his methodologies on sharh, and on presentinghadith as evidence, and on criticism of sanad and text, and on resolution of contradictionsamong hadiths are presented.The research is finalized with identifications and proposals on the subject.
Keywords: EMÎR; Hadis; HADİS USÛLÜ; Hadith Narration Analysis; İslam dini; RİVÂYET TAHLİLİ Emir; SAN’ÂNÎ; San’ani; Usool al-Hadith